2009
DOI: 10.1111/j.1469-1795.2009.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Landscape features and crustacean prey as predictors of the Southern river otter distribution in Chile.

Abstract: Understanding the processes that affect freshwater ecosystems at the watershed level is fundamental for the conservation and management of river otters. During 2 consecutive years, we surveyed the occurrence of the Southern river otter Lontra provocax and its main prey (crustaceans) in a watershed of 9900 km 2 in the Chilean temperate forest. We modeled predator and prey distributions with a variety of statistical techniques by relating a set of environmental predictors to species occurrence records. Otter and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
(41 reference statements)
0
10
0
2
Order By: Relevance
“…In fact, priority conservation actions should particularly focus on species whose ranges would become more fragmented or would shift into less protected and more human-impacted areas. For instance, we found that climate change would not affect the range extent of the endangered Latin American Lontra provocax (scenario RCP2.6-2050) but would increase range fragmentation, a factor that is already threatening this species (Sepulveda et al 2009).…”
Section: Discussionmentioning
confidence: 90%
“…In fact, priority conservation actions should particularly focus on species whose ranges would become more fragmented or would shift into less protected and more human-impacted areas. For instance, we found that climate change would not affect the range extent of the endangered Latin American Lontra provocax (scenario RCP2.6-2050) but would increase range fragmentation, a factor that is already threatening this species (Sepulveda et al 2009).…”
Section: Discussionmentioning
confidence: 90%
“…Like in the marine habitats, crustaceans play a key role in the diet of the southern river otter in freshwater habitats as well (Cassini et al ., ; Sepúlveda et al ., ), and lack of this kind of prey in southern Patagonian freshwater systems (Oyandel et al ., ) explains why otters were absent from the Cisne River study area, where minks resorted to hunting almost exclusively terrestrial prey, which comprised mostly one species of rodents, the long‐tailed colilargo Oligoryzomys longicaudatus .…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present article is to assess the feeding adaptive response of otters to the temporal and spatial distribution of non‐native fishes throughout its European range as well as the potential role played by this ‘new’ resource for otter conservation through a comprehensive review and analysis of available information on (i) occurrence of non‐native fishes in otter diet, (ii) history of freshwater fish introductions and (iii) current status of non‐native fishes in the countries for which sound otter diet data were available. Data were analysed using Random Forest Regression (RFR), a machine learning technique that is currently considered a promising technique in ecology (Franklin, 2010; Drew, Wiersma & Huettmann, 2011; Cheng et al ., 2012), useful to disentangle complex ecological phenomena (Schwartz et al ., 2006; Sepúlveda et al ., 2009; Davidson et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%